Law and gender in the ancient Near East and the Hebrew Bible - Peled, Ilan (Abingdon, Oxon Routledge, 2020)
This volume examines how gender relations were regulated in ancient Near Eastern and biblical law. The textual corpus examined includes the various pertinent law collections, royal decrees and instructions from Mesopotamia and Hatti, and the three biblical legal collections. Peled explores issues beginning with the wide societal perspective of gender equality and inequality, continues to the institutional perspective of economy, palace and temple, the family, and lastly, sex crimes. All the texts mentioned or referred to in the book are given in an appendix, both in the original languages and in English translation, allowing scholars to access the primary sources for themselves. Law and Gender in the Ancient Near East and the Hebrew Bible offers an invaluable resource for anyone working on Near Eastern society and culture, and gender in the ancient world more broadly
Introduction--The Societal Perspective: Social Status and Gender (In)equality-- The Institutional Perspective: Bureaucracy and Economy: The Palace, Temple, and Beyond-- The Familial Perspective: Regulation of Family Life-- The Individual Perspective: Morality and Sex Crimes-- Summary, Analysis and Conclusions.
All the texts mentioned or referred to in the book are given in an appendix, both in the original languages and in English translation --Publisher's website.
Includes bibliographical references and index.
Keywords: Women (Assyro-Babylonian law); Women (Jewish law)